The Forum : A Journal of Applied Research in Contemporary Politics (De Gruyter, 2003)
This journal provides a forum for professionally informed commentary on issues affecting contemporary American politics. This includes but is not limited to issues engaging parties, elections, and political participation; the news media, interest groups, Congress, the Presidency, and the Courts; trends in public finance, presidential popularity, congressional productivity; in contemporary, historical, or comparative perspective.